The Effect of Intellectual Capital on Firm Value with Financial Performance as an Intervening Variable: Pengaruh Intellectual Capital Terhadap Nilai Perusahaan dengan Kinerja Keuangan Sebagai Variabel Intervening - Rosi Adisciya Saffitri; Eny Maryanti (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine the effect of intellectual capital on firm value with financial performance as an intervening variable (study of companies listed on the Indonesia Stock Exchange for the 2016-2019 period). The sampling method used is purposive sampling method. The number of companies that were sampled in this study were 13 banking companies listed on the IDX in the 2016-2019 period. The data used is secondary data. The data analysis method used in this research is PLS (Partial Least Square) 3.2. The results of this study indicate that Intellectual Capital (X) has an effect on Firm Value (Y), Intellectual Capital (X) has an effect on Financial Performance (Z), Financial Performance (Z) has an effect on Firm Value (Y), Intellectual Capital (X) has an effect on to Firm Value (Y) with financial performance (Z) as the Intervening variable.